Mental Fatigue and Its Associated Factors among Coal Mining Workers after One Year of the COVID-19 Pandemic in Indonesia - Djamalus, Hendra; Utomo, Budi; Djaja, I Made; Nasri, Sjahrul M (UI Scholars Hub, 2021)
Mental fatigue among coal mining operators was related to driving activities that require high concentration. This study aimed to determine factors that contributed to mental fatigue among coal mine operators in Indonesia, specifically in Kalimantan and Sumatra, after a one-year COVID-19 pandemic. This cross-sectional study was conducted among 480 operators from two companies and seven sites. A self-administrated questionnaire in the Google Form was used to measure mental fatigue, the non-work-related factors (age, education, marital status, residence, and stress level), and work-related factors (working periods, shift pattern, type of shift, and work area in mining). The data analyzed using Chi-square and binomial logistic regression showed that the prevalence of mental fatigue was 32.3%. Operators with moderate stress and working in the pit area demonstrated a significant association with mental fatigue (p-va lue<0.001). Multivariable analysis showed that medium stress (AOR = 2.11; 95% CI = 1.41-3.15) and working in the pit (AOR = 2.27; 95% CI: 1.45-3.57) had a positive association with mental fatigue. Thus, the pit condition and stress levels were the dominant factors influencing mental fatigue and became points to manage mental fatigue in coal mining operators in Kalimantan and Sumatra.